EDUCATION MANAGEMENT REGARDING SOFT SKILLS BASED ON ETHICAL PRINCIPLES IN NURSING EDUCATION (Universitas Negeri Semarang, 2014)
Nursing ethics is an essential subject in nursing education to enhance nursing students competence. Nurses must think critically and enhance their soft skills to provide effective care whilst their performance with the expansion in role associated with the complexities of ethical issues. The purpose of this study was to describe education management regarding soft skills based on ethical principles in nursing education. The method of this research is Research and Development (R&D) that conducted at Health Polytechnic Semarang. Data were collected by self report questionnaires including Ethical Issues in Clinical Practice (EICP), Educational Management Regarding Soft Skills (EMRSS) and Focus Group Discussion (FGD) about Education Management Regarding Soft Skills In Nursing Education (SSNE). The results of this study showed that some factors influence including lecturer, nursing students and learning material in nursing ethics are dominant taking part to cultivate nursing students’ competence in caring. Proper preparation and active learning process contribute nursing students to become more understanding softs skills based on ethical principles. Indicator evaluation help the lecturer and nursing students to achieve the objectives of the learning in nursing ethics. The conclusion of this study is education management soft skills based on ethical principles cultivate the quality of nursing students’performance.